(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
In this article, the identification and development of the talent of primary school students, the unique activity of the child, the formation of individual talent, types of talent, special talent, ability, potential talent, obvious talent, hidden talent, education, intellectual opportunities, education and development of gifted students are described.